Pengaruh Pemberian Telur Ayan RAS Rebus Terhadap Kadar Hemaglobin Pada Ibu Nifa di Klinik Budi Mulia Medika - Wulandhari, Winda Y Harianja , Anggraini (STIKes Budi Mulia Sriwijaya, 2026)
Postpartum mothers have high risk of anemia because they lose a significant amount of blood during the childbirth, which can decrease their hemoglobin levels. Anemia worsens if the mother already has anemia during pregnancy. This condition can also occur due to physiological conditions of the hematological system, from pregnancy, childbirth, and the postpartum period. According to the WHO 2023, the incidence of anemia in pregnant women worldwide is 35.5%, and according to the Riskesdas 2018, the incidence of anemia in pregnant women in Indonesia is 48.9%. Anemia can be prevented by administering iron tablets and increasing the intake of foods high in protein and iron. This study aims to identify the effect of boiled chicken eggs on hemoglobin levels in postpartum mothers at the Budi Mulia Medika Clinic. This study was a quasi-experimental study with a pretest-posttest control group design. The study consisted of a treatment group given boiled chicken eggs and iron tablets, and a control group given iron tablets only. Hemoglobin levels were examined before (pretest) and after (posttest) of the intervention, which was carried out for 7 consecutive days. The population in this study was all 30 postpartum mothers who gave birth at the Budi Mulia Medika Clinic in February 2026. The sampling technique was accidental sampling. The analysis used in this study was the Paired T-Test and Independent T-Test. The Paired T-Test results obtained a ρ value of 0.00 <0.05, indicating a significant difference between the average hemoglobin levels before and after being given boiled chicken eggs to postpartum mothers. The Independent T-Test results obtained a ρ value of 0.04 <0.05, indicating a difference in hemoglobin levels between the group of postpartum mothers given boiled chicken eggs and the control group after being given treatment. It is hoped that the results of this study can be applied to postpartum mothers to increase hemoglobin levels by consuming chicken eggs. Keywords: Chicken Eggs, Hemoglobin Levels, Postpartum Mothers